Computer programs that assist in the analysis of qualitative data: an overview. - Tesch R (Qualitative Health Research, 1991)
Although no commercial software company has developed programs for the analysis of the social scientist's qualitative data, at least five such programs are currently available. They were created by scholars for their own research and then were packaged for use by others. This article first examines the main functions performed by these programs and then describes enhancements that let the user go beyond the basic collation of data segments according to themes or categories. A summary profile of each program is followed by a systematic comparison of the packages. Finally, a new type of program geared toward theory building is introduced, as are four packages currently being prepared for distribution. The article concludes with an assesment of the advantages and dangers of using computers as tools in the analysis of qualitative data.